2018
DOI: 10.1121/1.5020275
|View full text |Cite
|
Sign up to set email alerts
|

Swept-tone stimulus-frequency otoacoustic emissions: Normative data and methodological considerations

Abstract: Stimulus-frequency otoacoustic emissions (SFOAEs) are reflection-source emissions, and are the least familiar and perhaps most underutilized otoacoustic emission. Here, normative SFOAE data are presented from a large group of 48 young adults at probe levels from 20 to 60 dB sound pressure level (SPL) across a four-octave frequency range to characterize the typical SFOAE and describe recent methodological advances that have made its measurement more efficient. In young-adult ears, SFOAE levels peaked in the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The 95% confidence intervals (dashed lines) were generated through resampling of the data. Both age groups show the strongest SFOAEs between 1 and 2 kHz, consistent with past work (Abdala, Guardia, et al., 2018; Dewey & Dhar, 2017; Ellison & Keefe, 2005). Between 3 and 5 kHz, adults show higher levels than newborns, likely due to standing-wave interference in the ear canals of these adult subjects.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The 95% confidence intervals (dashed lines) were generated through resampling of the data. Both age groups show the strongest SFOAEs between 1 and 2 kHz, consistent with past work (Abdala, Guardia, et al., 2018; Dewey & Dhar, 2017; Ellison & Keefe, 2005). Between 3 and 5 kHz, adults show higher levels than newborns, likely due to standing-wave interference in the ear canals of these adult subjects.…”
Section: Resultssupporting
confidence: 90%
“…SFOAEs were evoked by 40 dB SPL pure tones swept logarithmically in a downward direction at 2 oct/s from f 2 = 0.5 to 8 kHz for both newborn and adult subjects. Four-frequency segments, each roughly one-octave wide, were stacked and presented concurrently for rapid data collection (see Abdala, Guardia, et al., 2018). A suppressor tone at 55 dB SPL was simultaneously presented at a frequency ratio of 0.95 (re: probe) and a modified interleaved suppression paradigm was utilized to extract SFOAEs (Shera & Guinan, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel method of sweep presentation was applied for efficiency: four sweep segments, each spanning 1.8 kHz, were presented concurrently as a stack. Recent work has shown that as long as there is at least a one-octave separation between stacked frequency segments, the impact on SFOAE amplitude and phase is negligible (Abdala et al, 2017); the advantage is that data collection time is cut to one-quarter the time required for a single sweep.…”
Section: Sfoaementioning
confidence: 99%